Effects of streamlined container design on control melting time of Phase Change Materials - Öztop, Hakan Fehmi F.; Sezgin, Elanur Baki (Taylor & Francis Inc, 2023)
Control of melting time for any chemical is important on behalf of the energy efficiency. In this study, two types of container with stepped geometry was designed to melt phase change materials (PCMs) under natural convection conditions. Volume of two containers are the same but one of geometry has streamlined corners. Thus, this two containers are compared to see the melting time under the same boundary conditions. The Paraffin was used as PCM and its melting temperature and latent heat of fusion are 53 & DEG;C and 243 kj/kg, respectively. In the first case, stepped geometry was used and then, this geometry was by streamlined corners for different aspect ratios and temperature differences. It is observed that the streamlined geometry can be used as passive control method for melting time. For the chosen geometry in the present study, the melting time is reduced at least 5% and energy efficiency can be improved.
Keywords: streamlined geometry; container; PCM; numerical; melting